The Impact of Sand and Stone Mining on the Width of the Kampar River in Tambang District, Kampar - Hadi, Syofian; Budijono, Budijono; Mulyadi, Aras (Jurnal Perikanan dan Kelautan, 2025)
The Kampar River has enormous benefits for people's lives, including the availability of non-renewable resources such as sand and stone, which are utilized without permission as raw materials for building. The high demand for river sand and stone and modern sand mining technology exacerbate environmental impacts, especially the width of the Kampar River. This study was conducted to determine the impact of changes in river width caused by illegal sand and stone mining activities in the Kampar River. This research uses a quantitative approach with direct observation methods, interviews, and literature studies. This research was conducted from May to August 2024 in Padang Luas Village, Terantang Village, Parit Baru Village, and Kualu Village, Tambang District, Kampar Regency. The results of this study indicate that illegal sand and stone mining activities in the Kampar River cause significant widening of the river, in addition to increasing turbidity and siltation of the river due to cliff collapse. The impact of changes in river width is worst in Parit Baru Village, which has the most mining locations compared to the other three villages. The highest turbidity value is found at station 3, and the shallowest river depth is at station 2. Illegal sand and stone mining has a real negative impact on the environment, especially on the physical condition of the Kampar River, which is marked by the siltation and widening of the river from year to year.